A neutral pH probe of rhodamine derivatives inspired by effect of hydrogen bond on pKa and its organelle-targetable fluorescent imaging. (October 2016) - Yu, Haibo; Li, Guli; Zhang, Bei; Zhang, Xinfu; Xiao, Yi; Wang, Jieqiong; Song, Youtao
Abstract: A neutral pH fluorescent probe (Rh-Met) based on rhodamine spirolactam is firstly developed according to the modulation strategy of hydrogen bonds on pKa values. The pKa value of Rh-Met was 6.81 (±0.06) and higher than that of other rhodamine spirolactams known. Rh-Met showed a 240-fold enhancement of fluorescence intensity at 585 nm with attenuation of pH values from 9.7 to 3.5. In addition, Rh-Met displayed an excellent selectivity and reversible response to hydrogen ion. And it was successfully employed for imaging endocellular hydrogen ion in mitochondria and lipid droplets. These results suggested that Rh-Met could be a potential tool to assess pH fluctuation in mitochondria and lipid droplets, and would promote many new opportunities for studying the biological effect of pH in living cells. Graphical abstract: Highlights: A neutral pH probe inspired by effect of hydrogen bond on pKa was developed. The pKa of probe was 6.81 and higher than that of other rhodamine spirolactams known. Probe displayed an excellent selectivity, organelle-targeting. It would be a potential tool to assess pH fluctuation in mitochondria of live cells.